Inflammation increases susceptibility of human small airway epithelial cells to pneumonic nanotoxicity - Wu, Zhuoran (2022)
Exposure to inhaled anthropogenic nanomaterials (NM) with dimension <100 nm has been implicated in numerous adverse respiratory outcomes. Although studies have identified key NM physiochemical determinants of pneumonic nanotoxicity, the complex interactive and cumulative effects of NM exposure, especially in individuals with preexisting inflammatory respiratory diseases, remain unclear. Herein, the susceptibility of primary human small airway epithelial cells (SAEC) exposed to a panel of reference NM, namely, CuO, ZnO, mild steel welding fume (MSWF), and nanofractions of copier center particles (Nano-CCP), is examined in normal and tumor necrosis factor alpha (TNF-α)-induced inflamed SAEC. Compared to normal SAEC, inflamed cells display an increased susceptibility to NM-induced cytotoxicity by 15-70% due to a higher basal level of intracellular reactive oxygen species (ROS). Among the NM screened, ZnO, CuO, and Nano-CCP are observed to trigger an overcompensatory response in normal SAEC, resulting in an increased tolerance against subsequent oxidative insults. However, the inflamed SAEC fails to adapt to the NM exposure due to an impaired nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated cytoprotective response. The findings reveal that susceptibility to pulmonary nanotoxicity is highly dependent on the interplay between NM properties and inflammation of the alveolar milieu.